(untitled) (Педагогіка вищої та середньої школи, 2008)
In this article the possibilities of emotional flexibility improvement as the teacher’s emotional culture index by means of school methodical work are examined the dependence between formed level of this complicated personality-oriented education and effectiveness of pedagogical work is exposed.